Middle Palaeolithic toolstone procurement behaviors at Lusakert Cave 1, Hrazdan valley, Armenia. Issue 91 (February 2016) - Frahm, Ellery; Feinberg, Joshua M.; Schmidt-Magee, Beverly A.; Wilkinson, Keith N.; Gasparyan, Boris; Yeritsyan, Benik; Adler, Daniel S.
Abstract: Strategies employed by Middle Palaeolithic hominins to acquire lithic raw materials often play key roles in assessing their movements through the landscape, relationships with neighboring groups, and cognitive abilities. It has been argued that a dependence on local resources is a widespread characteristic of the Middle Palaeolithic, but how such behaviors were manifested on the landscape remains unclear. Does an abundance of local toolstone reflect frequent encounters with different outcrops while foraging, or was a particular outcrop favored and preferentially quarried? This study examines such behaviors at a finer geospatial scale than is usually possible, allowing us to investigate hominin movements through the landscape surrounding Lusakert Cave 1 in Armenia. Using our newly developed approach to obsidian magnetic characterization, we test a series of hypotheses regarding the locations where hominins procured toolstone from a volcanic complex adjacent to the site. Our goal is to establish whether the cave's occupants procured local obsidian from preferred outcrops or quarries, secondary deposits of obsidian nodules along a river, or a variety of exposures as encountered while moving through the river valley or across the wider volcanic landscape during the course of foraging activities. As we demonstrate here, it is not the case that one particular outcrop or deposit attracted the cave occupants during the studied time intervals. Nor did they acquire obsidian at random across the landscape. Instead, our analyses support the hypothesis that these hominins collected obsidian from outcrops and exposures throughout the adjacent river valley, reflecting the spatial scale of their day-to-day foraging activities. The coincidence of such behaviors within the resource-rich river valley suggests efficient exploitation of a diverse biome during a time interval immediately preceding the Middle to Upper Palaeolithic "transition, " the nature and timing of which has yet to be determined for the region.